(untitled) (Economics and region, 2024)
The article thoroughly examines the theoretical and methodological foundations as well as the practical aspects of evaluating the value of startup projects in the context of European integration processes, which are becoming increasingly relevant for Ukraine. In particular, the focus is on analyzing the existing methods and approaches to evaluating startups employed in Ukraine and the countries of the European Union. A detailed comparative analysis was conducted, revealing key differences between Ukrainian and European practices, as well as the limitations of applying traditional evaluation methods in the context of the domestic market. Special attention is given to analyzing the barriers associated with infrastructure deficiencies, limited access to financing, and the absence of unified evaluation standards in Ukraine. Based on the study of European practices, approaches to evaluating innovative projects that have proven successful in EU countries have been systematized. Opportunities for their adaptation to the specifics of the Ukrainian market have been identified, considering industry conditions, startup development stages, and existing economic limitations. Within the study, an integrated model for evaluating startup projects has been developed, taking into account the specifics of the Ukrainian business environment and aligning with contemporary European standards. The proposed model integrates quantitative indicators, such as projected cash flows, profitability, and financial stability, with qualitative aspects, including innovation and strategic alignment with market demands. Additionally, a methodological toolkit has been proposed, enabling comprehensive evaluation of startups by considering industry-specific factors, project development stages, and current market conditions. It has been demonstrated that the application of this approach enhances the investment attractiveness of startups and improves their opportunities for attracting international investments. The necessity of implementing unified evaluation standards has been justified, which will facilitate the harmonization of Ukrainian and European approaches in the field of venture financing. The practical significance of the obtained results lies in their potential use by venture funds, investment companies, and startup accelerators for making informed decisions regarding investment in innovative projectsThe proposed methodological approaches can also be used for training and enhancing the qualifications of specialists in startup management. The research results lay the foundation for further harmonization of methodological approaches to evaluating startups in both national and international contexts, which will facilitate the integration of Ukrainian innovative projects into the global market.